Hubungan Faktor Host (Umur 6 Bulan-14 Tahun) Dan Keberadaan Vektor Dengan Kejadian Demam Berdarah Dengue di Wilayah Kerja Puskesmas Kedungmundu Semarang Relationship Of Host Factors (Ages 6 Months - 14 Years) And Existence Vector With Dengue Hemorrhagic - Luqman Zarkasyi; Martini Martini; Retno Hestiningsih (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Semarang city is endemic regions, with the highest incidence rate in the District Tembalang in 2014 (IR = 110.55 for 100.000 in population). Case of DHF in Kedungmundu Primary Health Service was just happen 2014 which amount 154 cases with 86% of cases in the age group of 6 months-14 years. The purpose of this study was to determine the relationship of host factors (age 6 months-14 years) and the existence of the vector with the incidence of DHF in Kedungmundu Primary Health Service Semarang. This type of research was quantitative with a case control approach. Total sample was 104 samples. Analysis of data using chi-square test. The results of this research showed that there were association using mosquito repellent (p=0.003), history of DHF illness (p=0.008), and the existence of larva (p=0.0001) with incidence of DHF. Meanwhile, there were no relationship habit of sleeping morning/noon (p=0.430), habit of sleeping afternoon (p=0.691), habit of hanging clothes (p=0.316), using of mosquito nets (p=0.339), and nutritional status (p=0.150) with incidence of DHF. It was advisable for the community to increase efforts to improve activities mosquito nest eradication (PSN), and for Kedungmundu Primary Health Service to increase efforts to control DHF, for example regular larva monitoring and thorough.